2017
DOI: 10.1177/1073110517720653
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Elicit Behavioral Health Patients' and Providers' Opinions on Health Records Consent

Abstract: A main objective of this study is to assess the opinions of 50 behavioral health patients on selective control over their behavioral and physical health information. We explored patients' preferences regarding current consent models, what health information should be shared for care and research and whether these preferences vary based on the sensitivity of health information and/or the type of provider involved. The other objective of this study was to solicit opinions of 8 behavioral health providers on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 16 publications
3
49
0
Order By: Relevance
“…43,44 While some of these studies include patients with mental health disorders, few include patients with SMI. 31,44,34 We found that the majority of mental health professionals supported patient-centered granular data sharing control for care and research (70%). Regarding the impact on coordination of care, many feel patients should be allowed to restrict access to sensitive data in justified contexts, such as to avoid discrimination from professionals outside the mental health care system.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…43,44 While some of these studies include patients with mental health disorders, few include patients with SMI. 31,44,34 We found that the majority of mental health professionals supported patient-centered granular data sharing control for care and research (70%). Regarding the impact on coordination of care, many feel patients should be allowed to restrict access to sensitive data in justified contexts, such as to avoid discrimination from professionals outside the mental health care system.…”
Section: Discussionmentioning
confidence: 96%
“…Three transcripts were randomly chosen for exploratory analysis of themes expected from previous literature. 19,21,30,31,34 Thematic analysis themes were identified through repetition and frequency in the transcripts. 33 Meaningful segments of conversation considered were the units for coding and analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One often suggested way to mitigate the ethical concerns around the sharing of personal data in a research framework is by giving participants granular consent options [37]. In a medical context, most patients prefer to have a granular control over which medical data to share and for which purposes [88,89], especially in the context of electronic medical records [90]. Furthermore, the GDPR requires that organizations handling personal data give the individual granular consent options for how their data is used [91].…”
Section: Granular and Speci C Consentmentioning
confidence: 99%
“…Generally, the current literature demonstrates that patients prefer more transparency and granular data control, but there is a disconnect between patient and provider perspectives. 19,18,[22][23][24][25][26] A survey-based study of over 1600 participants concluded that patients are most influenced by privacy concerns (significant negative path coefficient βPC = −0.160, p < .001) when deciding whether to share their health information. 27 Other studies showed that trust in providers is the motivating factor to share health data, including highly sensitive information, such as HIV.…”
Section: Introductionmentioning
confidence: 99%